Systemic risk and contagion in the commodity market: identifying volatility transmission during crisis periods - Szturo, Marek; Włodarczyk, Bogdan; Ionescu, George H.; Firoiu, Daniela; Braga, Vitor (Technological and Economic Development of Economy, 2025)
The commodity market is a key element of the global economy. It is influenced by the political and economic situation of the major participants on the supply and demand side, as exemplified by the geopolitical and economic situation related to the conflict in Ukraine. Another aspect of this influence is the close relationship between commodity markets and financial markets. Both factors contribute to the possibility of the commodity market becoming subject to contagion, resulting in the transfer of supply and demand shocks and volatility. The aim of this article is to identify the commodities that are the source of contagion (volatility) during the transmission of shocks and the increase of systematic risk in selected periods. Combining traditional network theory with vector autoregression (VAR) model, we aim to estimate systemic linkages as a measure of systemic risk and the contagion process underlying it. We used time series of commodity returns from the Refinitiv Eikon database to observe the relationships between commodities during crisis periods, starting from 2006. The results suggest that the commodities with the largest increase in volatility transmission compared to the pre-crisis period acted as a transmission gate for market shocks. First published online 12 December 2024